If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(8 + 4 + x) = 0 Combine like terms: 8 + 4 = 12 7(12 + x) = 0 (12 * 7 + x * 7) = 0 (84 + 7x) = 0 Solving 84 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + 7x = 0 + -84 Combine like terms: 84 + -84 = 0 0 + 7x = 0 + -84 7x = 0 + -84 Combine like terms: 0 + -84 = -84 7x = -84 Divide each side by '7'. x = -12 Simplifying x = -12
| Y=4x-b | | 91-166=-8(-4y)-17(2y)+y | | X=65.5 | | 5y^2-7=42 | | 3/4b=46.50 | | 45+20+0.55x=45+0.65x | | 5x+(4)(-5)=-20 | | 46.50b-3/4 | | n-20.64=-6.64 | | X+5x+y+3y+5-2= | | 600=m-12+m | | 7(-3x-1/7) | | 2.78=.6*x | | y-13=3(x-5) | | 5(n+-11)=-16 | | 49x^2+70x=25 | | x=60/100 | | h=-16t^2+11t+85 | | 10(4+-4)= | | 11x+9y=5 | | 0.99+36x=1.39 | | 0.99-36x=1.39 | | (4*3)+(4*x)=36 | | 2(3x)=2x(x) | | S+(S-22)=S+46 | | 8.6x+1.3x=9.9 | | y=0.43x+33 | | 2.4x-0.4x=68 | | y=0.43+33 | | 8.75+9=12.5t+12 | | 3-(x-2)=4 | | 4r-6= |